Characterization of small ruminants in the Mitundu area, Lilongwe, Malawi - Kamwanja, L.A.; Ayvade, J.A.; Makhambera, T.P.E. (1985)
A survey was conducted between December 1984 and June 1985 to determine the sex, live and dressed weight, organ weight and the seasonal variation in small ruminants slaughtered at Mitundu, Central Malawi. Least numbers (2-6 per week) were slaughtered between February and April: numbers varied from 8-20 per week the rest of the time. Socio-economic reasons contributing to this variation are discussed. Females (67 per cent of animals slaughtered) were heavier than males (25.7 ± 0.47, 19,6 ± 0.81 and 21.7 ± 0.83 kg for females, entire males and castrates respectively). More than 60 per cent of slaughtered females were over 32 months of age while 80 per cent of males were less than 24 months old. Slaughtered males were 44 per cent and 56 per cent castrate and entire respectively. The dressing percentage ranged from 52.3 and 55.1. Weights of various organs and their contribution to live and dressed weight were similar within and between species except that rams had heavier testes (0.66 ± 0.03 kg) than bucks (0.42 ± 0.01 kg). Reproductive and growth potential of sheep (Dorper and local crosses) on natural pastures and Chloris gayana were also investigated. Twinning rate of ewes was 2.2 per cent and lambing interval was 255 ± 13.5 days suggesting that post-partum anoestrus averaged 105 days. Ram and ewe lamb birth weights averaged 2.63 ± 0.19 and 2.65 ± 0.14 kg. Birth weight of lambs was 8.8 per cent the liveweight of ewes.